Night eating and binge eating disorder in employees of an academic institution - Pereira Peixoto Maciel, Ana Ruth; Amorim dos Santos, Arianny; Garcia e Silva, Emerson Iago; Bazílio de Omena Messias, Cristhiane Maria (O Mundo da Saúde, 2018)
The present study aimed to evaluate the incidence of nocturnal eating and binge eating sydrome in employees of a public institution of higher education. A cross-sectional analytical study was developed between August 2015 and July 2016. The initial sample consisted of approximately 150 contracted employees of both sexes linked to the institution in the year 2015. The final sample consisted of 53 employees. The volunteers received the Informed Consent Form as a way of attesting to their participation in the present study. Afterwards, they were identified by sector and function, in order of the forms: Night Eating Questionnaire (NEQ), Binge Eating Scale (BES) and The Three Factor Eating Questionnaire (TFEQ-R21). There was no statistically significant association between the analyzed variables: gender and NEQ, BES and TFEQ-R21. No incidences of cases in this study were observed, which could have been masked in the face of the controversy surrounding this subject, due to the omission of some relevant information needed to characterize the subjects as at risk for the development of the syndrome. There is a pertinent need for further studies in order to understand the genesis of and the intrinsic relationships with other pathophysiological processes; especially since, the syndrome is linked to aspects that involve hunger and satiety, changes in food rhythm and sleep/wakefulness.